2021
DOI: 10.1057/s41599-021-00747-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-use plastic packaging in the Canadian food industry: consumer behavior and perceptions

Abstract: Single-use plastic food packaging is a major contributor to the global solid waste problem. Although the food industry is developing strategies to reduce single-use plastic packaging, it needs to better understand consumer awareness and attitudes about the issue. As consumer awareness about single-use plastic waste outpaces private sector practices, this study considered personal motivation factors, government policies, and innovative solutions related to single-use plastic food packaging. This Canada-wide stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 50 publications
8
67
0
Order By: Relevance
“…The CDC in the United States and the scientific community abroad have continuously sought to reassure the public that consuming food carries no risk of transmission of COVID-19, and that the virus itself would not survive on food packaging for an extended time. Canadian consumers were significantly concerned about contracting the virus directly from foods and food packaging [63]. Consumers have stigmatized portions of the food system because of not having sufficient or reliable epidemiological knowledge of the virus [64].…”
Section: Virus Epidemiologymentioning
confidence: 99%
“…The CDC in the United States and the scientific community abroad have continuously sought to reassure the public that consuming food carries no risk of transmission of COVID-19, and that the virus itself would not survive on food packaging for an extended time. Canadian consumers were significantly concerned about contracting the virus directly from foods and food packaging [63]. Consumers have stigmatized portions of the food system because of not having sufficient or reliable epidemiological knowledge of the virus [64].…”
Section: Virus Epidemiologymentioning
confidence: 99%
“…Prior to the current situation, a large-scale outbreak of Ebola in several African nations and further abroad in 2014 was met with a rapid response from international public health organizations including the World Health Organization (WHO, 2015;Walker et al, 2021). Here we can see a response from the sort of public health apparatus which arose in the wake of the Spanish flu epidemic, specifically in food safety during an epidemic.…”
Section: Historical Contextmentioning
confidence: 99%
“…Nevertheless, there was a third group that, although also conscientious about the implications of single-use plastics, still sometimes use them. A study conducted with Canadian consumers [26] revealed that practically all of the participants (around 94%) felt motivated to reduce the consumption of foods packed using single-use plastic. In this study, the authors also said that environmental concerns were more critical than food safety from the point of view of consumers.…”
Section: Introductionmentioning
confidence: 99%